Resistência à fadiga de junta circunferencial de um tubo API 5L x 70 em contato com etanol - Giorgetti, Vinícius (2016)
Circumferential field-welding joints of oil pipelines are susceptible to defects that may lead to failures when in operation. The type of product to be transported is an important factor in the evaluation of environment-induced cracking, especially of welded joints, where fatigue cracks may originate at points of high stress concentration. In Brazil, the construction of a long distance pipeline has been started in 2014, to transport sugarcane ethanol, which is currently widely mixed with motor fuels. In this work a circumferential joint of an API 5L X70 line pipe was evaluated by hardness, tensile and impact tests; the microstructure was observed by optical microscopy in the different regions of the welded joint and the fractured surfaces were analyzed by SEM. The material of the tube was classified according to API 5L specifications and the welded regions showed hardness distribution and microstructures in agreement with the literature. The fracture surface of the welding metal after tensile and impact tests indicated that the presence of welding discontinuities may affect strongly the fracture behavior, leading to embrittlement, especially under impact testing. The susceptibility of welded joints to stress corrosion cracking (SCC) in a simulated fuel-grade ethanol (SFGE) environment was evaluated by slow strain rate (SSR) and fatigue crack growth (FCG) tests. The tests were designed to promote crack propagation through the heat-affected zone (HAZ) or through the weld metal (WM) of a circumferential weld on an API X70 steel pipe. The SSR tests in SFGE showed reduction of elongation to failure and mixed fracture, with clear signs of SCC in both the regions of the weld. The FCG tests demonstrated that the time-dependence of corrosion fatigue interactions may involve alternating periods of increasing and decreasing crack growth rates throughout the test. Acceleration of crack propagation due to SCC predominated in the WM and deceleration predominated in the HAZ.